Ableist contours of Down syndrome in Australia: Facebook attitudes towards existence and parenting of people with Down syndrome. (June 2021) - Johnson, Belinda; West, Raelene
The emergence of online disability hate speech on social media platforms is the latest form of ableist expression. This was highlighted when an alarming amount of negative attitudinal responses emerged towards people with Down syndrome and their parents on the 60 Minutes Facebook platform to their segment 'Does Australia really want to see the end of Down syndrome?' This article analyses the varying contours of ableism within these responses. The responses could be categorised into three broad themes: the construction of Down syndrome as an economic burden on society and a drain on public resources; social attitudes to Down syndrome; and bias related to information provided by the medical profession to pregnant women with a high probability of a Down syndrome birth. These findings allowed us to interrogate what this means in terms of how Australians view difference associated with Down syndrome, and to consider the operationalisation of ableism within the Australian social landscape.